Determination of multiple mycotoxin residues in Panax ginseng using simultaneous UPLC‐ESI‐MS/MS. Issue 4 (7th March 2018) - Bi, Bo; Bao, Jingshan; Xi, Guangsheng; Xu, Yonghua; Zhang, Lianxue
Abstract: Presented here is an optimized and validated high‐throughput method for the simultaneous determination of 11 different classes of mycotoxins from the popular traditional Chinese medicine Panax ginseng . The selected mycotoxins included the aflatoxins B1, B2, G1, and G2 and the fumonisins B1 and B2, as well as CIT, HT‐2, T‐2, zearalenone, and ochratoxin A. This high‐throughput analysis was achieved using a simple pretreatment procedure with no clean‐up and featured the convenient and fast‐speed determination provided by LC‐MS/MS within 12 min, for the qualitative and quantitative analysis of 11 selected mycotoxins. We sought to optimize the MS parameters and UPLC conditions and multiple reaction monitoring was used in both positive and negative electrospray ionization mode. Matrix‐matched calibration was applied for the quantification of the 11 mycotoxins in P. ginseng, within the range of 0.5–250 ng/ml. Validation of this method was performed by analyzing samples spiked at three different levels (low, medium, and high). The limits of detection and quantification of the method was within the ranges of 0.25–50 ng/ml and 0.1–25 ng/ml, respectively. Finally, this analytical method was successfully used to assess 10 separate batches of P. ginseng samples obtained from local markets and only one sample detected FB2 . Practical applications: Panax ginseng has been widely used as a highly valued and popular medicinal herb for thousands of years. The potential presence of multiple mycotoxins in P. ginseng is a key issue for its safety and has caused great public concern. In this study, a fast and easy UPLC‐ESI‐MS/MS analytical method coupled with a simple pretreatment procedure was established and validated for simultaneous determination of 11 of the most crucial mycotoxins (AFG2, AFG1, AFB2, AFB1, CIT, FB1, FB2, HT‐2 T‐2 ZON, and OTA) in 10 batches of P. ginseng samples, to ensure the quality of TCMs as well as protect the health of humans and animals.